Effects of Cocaine and Withdrawal on the Mouse Nucleus Accumbens Transcriptome - Eipper-Mains, Jodi E. (2012)
Genetic association studies, pharmacological investigations, and analysis of mice lacking individual genes have made it clear that cocaine administration and withdrawal have a profound impact on multiple neurotransmitter systems. The GABAergic medium spiny neurons of the nucleus accumbens (NAc) exhibit changes in the expression of genes encoding receptors for glutamate and in the signaling pathways triggered by dopamine binding to G-protein coupled dopamine receptors. Deep sequence analysis provides a sensitive, quantitative and global analysis of the effects of cocaine on the NAc transcriptome. RNA prepared from the NAc of adult male mice receiving daily injections of saline or cocaine, or cocaine followed by a period of withdrawal, was used for high-throughput sequence analysis. Changes were validated by qPCR or Western blot. Based on pathway analysis, a preponderance of the genes affected by cocaine and withdrawal were involved in the cadherin, heterotrimeric G-protein, and Wnt signaling pathways. Distinct subsets of cadherins and protocadherins exhibited a sustained increase or decrease in expression. Sustained down-regulation of several heterotrimeric G-protein β- and γ-subunits was observed. In addition to altered expression of receptors for small molecule neurotransmitters, neuropeptides and endocannabinoids, changes in the expression of plasma membrane transporters and vesicular neurotransmitter transporters were also observed. The effects of chronic cocaine and withdrawal on the expression of genes essential to cholinergic, glutamatergic, GABAergic, peptidergic, and endocannabinoid signaling are as profound as their effects on dopaminergic transmission. Simultaneous targeting of multiple withdrawal-specific changes in gene expression may facilitate development of new therapeutic approaches that are better able to prevent relapse.